2020
DOI: 10.1101/2020.06.28.20136168
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

SARS-CoV-2 & Pediatric Mental Health: A Review of Recent Evidence

Abstract: SARS-CoV-2 was declared a global pandemic by the World Health Organization (WHO) and was met with lockdown policies to curb the spread of the disease. This meant that 890 million students in 114 countries would be affected by the closure of their educational institutes, affecting their mental health. Mental health disorders are suggested to have a well-correlated link to suicide which is the third most leading cause of death worldwide amongst children aged 15-19 years. According to WHO, 'health is a state of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
15
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(15 citation statements)
references
References 16 publications
0
15
0
Order By: Relevance
“…Most reviews included a wide range of primary study designs ( Table 1 ). Some specified eligibility criteria for study design, for example relating to the minimum sample size [ 20 , 21 ], assessment of mental health problems [ 19 , 22 ] or quality of reporting and study conduct [ 18 ]. Fourteen reviews excluded studies not conducted in English.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Most reviews included a wide range of primary study designs ( Table 1 ). Some specified eligibility criteria for study design, for example relating to the minimum sample size [ 20 , 21 ], assessment of mental health problems [ 19 , 22 ] or quality of reporting and study conduct [ 18 ]. Fourteen reviews excluded studies not conducted in English.…”
Section: Resultsmentioning
confidence: 99%
“…Different reviews reported estimates of 19 to 37% for anxiety, 35 to 44% for depression, 6% for PTSD, 40% for symptoms of psychological distress, and 17% for acute stress disorder [ 22 , 30 ]. Reports of mental health symptoms in college students included anxiety, depression, substance abuse, sleeping disorders, and eating disorders [ 21 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations